Potential of Lemna gibba L. and Lemna minor L. for accumulation of Boron from secondary effluents - Tatar, Sule Yuksel; Obek, Erdal (Elsevier, 2014)
Aquatic plants are quite effective in removal of pollutants which cannot be removed in secondary treatment. Lemna gibba L. and Lemna minor L. among the aquatic plants were investigated for the removal of boron from the secondary waste water. Differences in Boron uptake were seen in the chosen aquatic macrophytes. Although boron is at low concentration in water, the bioaccumulated concentrations in Lemna minor L. and Lemna gibba L. were at high levels of between 140 mg Bg 140 -1and 274 mgB g(-1), and 381 mgB g(-1) 523 mgB g(-1) respectively. From these results, it was understood that Lemna gibba L. is more prone to accumulate boron compared to Lemna minor L. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Effluent; Boron; Phytoremediation; duckweed; Accumulation